Theoretical approach to electrodiffusion of shallow donors in semiconductors: I. Stationary limit - Kashirina, N.I.; Kislyuk, V.V.; Sheinkman, M.K. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1998)
Analysis is made for the possibility of redistribution of mobile point defects in a semiconductor after its exposure to the electric field till the stationary conditions in the crystal are reached. Two different ways of applying the voltage are considered: (i) directly to the sample, (ii) to a capacitor, with the sample located between the plates. This model is applicable also to the electric field of any nature, whether external or internal, e.g. that arisning at the metal-semiconductor interface. Дається аналіз можливості розподілу рухомих точкових дефектів в напівпровіднику після дії на нього електричного поля до встановлення стаціонарних умов. Розглядаються два способи прикладання напруги: а) безпосередньо до зразка, б) до обкладинок конденсатора, між якими поміщається зразок. Модель також можна застосовувати для електричних полів будь-якої природи . як зовнішніх так і внутрішніх, що виникають, наприклад, на контакті метал-напівпровідник. Приводится анализ возможности распределения точечных дефектов в полупроводнике после воздействия на него электрического поля до установления стационарных условий. Рассматривается два способа приложения напряжения: а) непосредственно к образцу, б) к обкладкам конденсатора, между которыми помещается образец. Модель также применима для электрических полей любой природы как внешних так и внутренних, возникающих, например, на контакте металл-полупроводник.